CXCL‐10 and Interleukin‐6 are reliable serum markers for vitiligo activity: A multicenter cross‐sectional study. (1st December 2017) - Abdallah, Marwa; El‐Mofty, Medhat; Anbar, Tag; Rasheed, Hoda; Esmat, Samia; Al‐Tawdy, Amira; Fawzy, Marwa M.; Abdel‐Halim, Dalia; Hegazy, Rehab; Gawdat, Heba; Bassiouny, Dalia; Ibrahim, Mona A.; et al.
Summary: This cross‐sectional multicenter study aimed to evaluate serum CXCL‐10, as an activity marker for vitiligo, and compare it with other putative serum and tissue markers. Serum CXCL‐10 was compared to interferon gamma (IFN‐γ), interleukin 6 (IL‐6), and IL‐17 using ELISA in 55 non‐segmental vitiligo patients (30 active and 25 stable) and 30 healthy controls. Marginal skin biopsy was taken for immunohistochemical evaluation of CD8+T cells and CXCL‐10+ve cells. Serum levels of CXCL‐10, IL‐17, and IL‐6 were elevated in all vitiligo patients compared to controls ( p < .05). All investigated serum markers were higher in active versus stable vitiligo. Tissue expression of CXCL‐10+ve cells and CD8+ve T cells was stronger in vitiligo patients compared to controls, and tissue CXCL‐10+ve cell expression was stronger in active versus stable cases. Positive correlations were noted between the different serum and tissue markers. CXCL‐10 was the most specific, whereas IL‐6 was the most sensitive serum marker to distinguish active from stable disease.